Evaluation of the long-term effects of COVID-19 on pulmonary functions in recovered patients - K Naja; Durga Shankar Meena; Deepak Kumar; Naveen Dutt; Gopal K. Bohra; Ravisekhar Gadepalli; Mithu Banerjee; Mahendra K. Garg; Sanjeev Misra (Journal of Family Medicine and Primary Care)
Background: It is documented that COVID-19 survivors have prolonged morbidity and functional impairment for many years. Data regarding post-COVID-19 lung functions is lacking from the Indian population. We aim to evaluate the lung functions in such patients after 3–6 months of hospital discharge. Methods: In this prospective observational study, patients were assessed 3 to 6 months post-discharge and underwent standardized pulmonary function tests (PFTs) and CT Thorax if required. The following parameters were measured and correlated with the disease severity: Forced Vital Capacity (FVC), Forced Expiratory Volume in the First Second (FEV1), Forced Expiratory Flows at 25 and 75% of FVC (FEF25%-75%), Peak Expiratory Flow (PEF) and FEV1/FVC. Results: A total of 52 post-COVID-19 patients were enrolled in the study, with a median age of 43 years (78.8% males). 44.2% of patients had mild disease, 26.9% had moderate disease and 23.1% had severe disease at hospital admission. A restrictive pattern was seen in 20.8% of patients. The mean value of FEV1 and FVC decreased as the disease severity increased. FEV1: mild-3.21 ± 0.71, moderate-2.62 ± 0.61 and severe- 2.51 ± 0.72, P = 0.02; FVC: mild-3.69 ± 0.81, moderate-3.04 ± 0.71 and severe- 2.93 ± 0.87, P = 0.02. After adjusting the confounding factors, the mean pulmonary function values were lower in the patients who required oxygen support, with a significant difference in FEV1, FVC, PEF and FEF 25–75% with P values of 0.025, 0.046, 0.028 and 0.007, respectively. 66.67% had abnormal HRCT findings. Age and high LDH were correlated with HRCT abnormality with P values of 0.015 and 0.024. Age >50 years was found to be an independent predictor of the subsequent development of abnormality on the HRCT thorax. Conclusions: Patients with COVID-19 pneumonia, which required oxygen, especially severe disease at the time of hospitalization, had a higher rate of abnormal spirometry than patients with mild symptoms. Follow-up CT scans obtained within six months of disease onset showed abnormalities in more than half of patients, particularly elderly patients.